Manufacturing lot affects polyethylene tibial insert volume, thickness, and surface geometry. (August 2013) - Teeter, Matthew G; Milner, Jaques S; MacDonald, Steven J; Naudie, Douglas DR
To perform wear measurements on retrieved joint replacement implants, a reference geometry of the implant's original state is required. Since implants are rarely individually scanned before implantation, a different, new implant of the same kind and size is frequently used. However, due to manufacturing variability, errors may be introduced into these measurements, as the dimensions between the retrieved and reference components may not be exactly the same. The hypothesis of this study was that new polyethylene tibial inserts from different manufacturing lots would demonstrate greater variability than those from the same lot. In total, 12 new tibial inserts of the same model and size were obtained, 5 from the same lot and the remainder from different lots. The geometry of each tibial insert was obtained using microcomputed tomography. Measurements of tibial insert volume, thickness, and three-dimensional surface deviations were obtained and compared between tibial inserts from the same and different manufacturing lots. Greater variability was found for the tibial inserts from different manufacturing lots for all types of measurements, including a fourfold difference in volume variability (p < 0.001) and a maximum of 0.21 mm difference in thickness (p < 0.001). Investigators should be aware of this potential confounding error and take steps to minimize it, such as by averaging together the geometries of multiple new components from different manufacturing lots for use as the reference geometry.